PENINGKATAN HASIL BELAJAR DAN KONSENTRASI MURID DALAM MATERI AKSARA JAWA MELALUI PENERAPAN MEDIA GAME EDUKATIF - Pratama, Mandala; Anggraeni Hadhi Saputri; Cindy Joe Sanjun; Murfiah Dewi Wulandari; Widyaningrum Yudi Rahayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning Javanese script is challenging due to its differences from Latin letters, affecting students' learning outcomes and concentration. This study aims to enhance learning outcomes and concentration using educational game media. The research employs Classroom Action Research (CAR) with the Kemmis and McTaggart model in two cycles, involving 22 third-grade students at SD Muhammadiyah 22 Sruni. Results show a significant improvement in learning outcomes, with average scores increasing from 54.81 (pre-cycle) to 58.40 (cycle I) and 84.54 (cycle II). The highest scores rose from 93 (pre-cycle) to 95 (cycle I) and 100 (cycle II). Student concentration also improved, with optimal concentration rates increasing from 36.37% (pre-cycle) to 68.19% (cycle I) and 95.56% (cycle II). These findings demonstrate that educational games enhance students’ engagement and comprehension of Javanese script. The study contributes to educational science by proving that interactive technology-based media can improve learning effectiveness, particularly for difficult subjects. Implementing educational games provides an engaging learning experience, making it an effective strategy for teachers to optimize student participation and understanding.